2018
DOI: 10.1108/ijoa-03-2017-1141
|View full text |Cite
|
Sign up to set email alerts
|

Organising household consumption and occupational proportions

Abstract: PurposeThe purpose of this paper is to contribute to the occupational status and entrepreneurship research in developing countries by proposing that there are implications for household consumption depending on the occupational status proportion of households. When the occupational proportion of the household changes, household consumption is affected. This effect also changes depending on what quantile level the household is in terms of household consumption. Design/methodology/approachThe paper makes use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…However, it is often somewhat unclear if the employment and pay disparities that exist along ethnic lines are as a result of negative stereotypes (Ruhlandt et al 2020). Research from Asia also shows that ethnic minorities often earn less than the dominant ethnic group (Kabeer 2006), and similar results have been found in Africa (Olarewaju 2018).…”
Section: Disproportionate Employment and Pay Disparitiessupporting
confidence: 63%
“…However, it is often somewhat unclear if the employment and pay disparities that exist along ethnic lines are as a result of negative stereotypes (Ruhlandt et al 2020). Research from Asia also shows that ethnic minorities often earn less than the dominant ethnic group (Kabeer 2006), and similar results have been found in Africa (Olarewaju 2018).…”
Section: Disproportionate Employment and Pay Disparitiessupporting
confidence: 63%
“…The insecurity is contributing to low agricultural productivity, as well as affecting household consumption. Several other factors have also been found to affect household consumption, such as educational levels, location, earnings uncertainty, and more (Olarewaju, 2018). Dreze and Srinivasan (1997), as quoted in Olarewaju (2018), reported that in India households that are headed by a female are more likely to suffer from lower household consumption than those headed by a male.…”
Section: Asian Development Policy Reviewmentioning
confidence: 99%
“…The consumption unit of society has mostly been defined as a unit that acquires inputs for immediate and future consumption (Olarewaju, 2018). Households usually participate in the labour force to acquire the means of consumption of goods and services.…”
Section: Introductionmentioning
confidence: 99%
“…Government budgetary corruption in Nigeria is a serious problem and a mechanism politicians and civil servants use in order to funnel public resources (Ogunyemi, 2017; Olarewaju, 2016). Some well‐known examples of budgetary corruption in Nigeria include the expenditure of billions of US dollars to resuscitate the power and transport sectors of the country but with very little to show for the vast sums expended (Okpala, 2012; Olarewaju, 2018). Extant research shows that the budgetary medium is currently used by Nigerian government officials and public officers to regularly misappropriate public funds (Ajibolade & Oboh, 2017; TransparencyInternational, 2019).…”
Section: Contextmentioning
confidence: 99%